Design of nonlinear control systems with the highest derivative in feedback - Yurkevich, Valery D. (Series on stability, vibration, and control of systems., 2004)
This unique book presents an analytical uniform design methodology ofcontinuous-time or discrete-time nonlinear control system design whichguarantees desired transient performances in the presence of plantparameter variations and unknown external disturbances.